Host PrP glycosylation: a major factor determining the outcome of prion infection. - Nadia L Tuzi; Enrico Cancellotti; Herbert Baybutt; Lorraine Blackford; Barry Bradford; Chris Plinston; Anne Coghill; Patricia Hart; Pedro Piccardo; Rona M Barron; Jean C Manson (PLoS Biology, 2008)
The expression of the prion protein (PrP) is essential for transmissible spongiform encephalopathy (TSE) or prion diseases to occur, but the underlying mechanism of infection remains unresolved. To address the hypothesis that glycosylation of host PrP is a major factor influencing TSE infection, we have inoculated gene-targeted transgenic mice that have restricted N-linked glycosylation of PrP with three TSE strains. We have uniquely demonstrated that mice expressing only unglycosylated PrP can sustain a TSE infection, despite altered cellular location of the host PrP. Moreover we have shown that brain material from mice infected with TSE that have only unglycosylated PrP(Sc) is capable of transmitting infection to wild-type mice, demonstrating that glycosylation of PrP is not essential for establishing infection within a host or for transmitting TSE infectivity to a new host. We have further dissected the requirement of each glycosylation site and have shown that different TSE strains have dramatically different requirements for each of the glycosylation sites of host PrP, and moreover, we have shown that the host PrP has a major role in determining the glycosylation state of de novo generated PrP(Sc).